Mitochondrial DNA analyses found five novel mutations in idiopathic epilepsy patients. Issue 2 (3rd July 2019) - You, Cuiping; Tao, Rui; Su, Quanping; Lu, Yucheng; Wang, Long; Liu, Shu; Wang, Lifen; Wang, Lijuan; Xue, Fuzhong; Che, Fengyuan
Abstract: Epilepsy is a common and chronic neurological disease with a high degree of genetic heterogeneity. The etiology and pathogenesis of the disease have not been fully understood. Many studies suggested that there was a reciprocal relationship between mitochondrial dysfunction and epilepsy, but few studies focused on the mitochondrial genome (mtDNA) of the epilepsy patient which was extremely important for the mitochondrial function. In our study, we obtained complete mtDNA sequences of 27 idiopathic epilepsy patients and healthy people, and compared the sequence data with 30, 000 GenBank sequences including 277 Han Chinese mtDNA sequences. We analyzed each variant that might be related to disease and examined the statistically significant variant in more than 300 patients and healthy people. Ultimately, we identified 27 variants which were reported to be associated with diseases, 4 rare variants (321T > G, 15973 T > C, 3897C > A, 12580 C > T), and a nonsynonymous variant (3571 C > T) which was predicted to be damaging. Although no variant was found to be significantly associated with epilepsy, our study provided a new insight into epilepsy study on an aspect of the mitochondrial genome.